ERCC1 plays an important role in predicting survival outcomes and treatment response for patients with HNSCC: A meta-analysis. Issue 5 (May 2015) - Xuelei, Ma; Jingwen, Huang; Wei, Du; Hongyu, Zhuo; Jing, Zhang; Changle, Shi; Lei, Liu
Summary: Background: Excision repair crosscomplementing-1 (ERCC1) has been reported to play a prognostic role and may indicate the treatment response in patients with head and neck squamous carcinoma (HNSCC). Nevertheless, the strength of evidence of ERCC1 predicting these two clinical outcomes are still controversial. Methods: Potentially eligible studies were retrieved using PubMed, Embase and Medline. Basic clinical characteristics of patients and statistical data with the survival data were collected. Then a meta-analysis model was established to investigate the correlation between over-expression of ERCC1 and survival outcome in HNSCC patients as well as to determine whether the treatment response is dependent on expression stature of ERCC1 or not. Results: 17 eligible studies and 1263 patients were yielded in our meta-analysis. The pooled HRs with 95% confidence intervals (CIs) for OS and PFS were 2.14 [1.51, 3.05] and 2.60 [1.98, 3.42], respectively. In terms of subgroup analysis, race was found to be a significant factor divided for these analyses, and the pooled HRs for the Asian subgroup are 2.97 [2.05, 4.32] and 2.75 [1.82, 4.13] respectively. In non-Asian subgroup, Pooled HRs indicate the predict role for PFS 2.42 [1.60, 3.66], but no value for OS ( P < 0.05). With regard to treatment response, the pooled ORs were 3.04 [1.99, 4.62]. Results from subgroup analysis that divided by race further showed that pooled ORs in Asian group were 3.95 [2.30, 6.78] and 1.93 [0.97, 3.84] in non-Asian group. Conclusion: ERCC1 could be a fine prognostic factor of HNSCC and can also prompt the treatment response, which might be proven by further multicenter clinical trials.